Bilateral Proximal Tibia Stress Fractures through Persistent Physes. (6th December 2018) - Carroll, John J.; Kelly, Sean P.; Foster, James N.; Mathis, Derek A.; Alderete, Joseph F.
Abstract : Introduction . Fatigue fractures are stress fractures resulting from repetitive trauma in areas of stress concentration. Prior case reports and studies have described stress fractures through persistent physes about the olecranon and distal fibula, as evidenced by hyaline cartilage on histologic analysis. However, there have been no documented proximal tibia stress fractures through persistent physes. Case Presentation . A 29-year-old military male basic trainee with varus alignment about his knees suffered bilateral medial tibial plateau stress fractures several weeks into military basic training. He underwent radiographic and laboratory evaluation of his stress fractures and eventual operative fixation of his bilateral tibial plateau fractures. Intraoperative specimens obtained from the fracture sites distal to the articular surface demonstrated abnormal fibrous appearing tissue. Histology demonstrated the presence of hyaline cartilage. Discussion . A 29-year-old military male basic trainee had bilateral proximal tibia stress fractures through persistent physes confirmed with biopsies demonstrating hyaline cartilage. Our belief is that the patient's persistent physes placed him at a greater risk for stress fractures and these may benefit from fixation in soldiers and athletes.